Notification of crop varieties and registration of germplasm - Shinde, M.S. (The Indian Journal of Genetics and Plant Breeding, 2016)
CSV 30F is a kharif forage sorghum single cut varietyderived through pedigree method from a cross NSS223 x NARI 111. It was identified for single cut forageby 43rd Annual Sorghum Group Meeting held atHyderabad on 21st to 23rd April 2013 at National levelcomprising the states of Haryana, Punjab, Rajasthan,Gujarat, Uttarakhand and Uttar Pradesh of Zone-I andMaharashtra and Karnataka and Tamil Nadu of ZoneII. The variety was subsequently notified by CentralSub-committee on Crop Standards, Notification andRelease of Varieties for Agricultural crops videnotification number S. O. 1919 (E) dated 31/7/2014.CSV 30F is tall variety with an average plant heightaround 267 cm. It flowers in 76 days after germination.Leaves are green in colour with white midrib. Earheadsare semi loose and oval in shape with round, pearlywhite grain colour. The grains are one fourth coveredby glumes. It has a better forage quality such as protein(8.07%, 9.67 q/ha), IVDMD (50.2%), digestible drymatter (57.6 q/ha) and low HCN (56.5 ppm) contents